Decree lifting excommunication latae sententiae of the bishops of the society of St. Pius X Canon 1382 - Katholische Kirche Kongregation für die Bischöfe (2009)
"Pope Benedict XVI remitted the excommunications of four bishops ordained against papal orders in 1988 by the late French Archbishop Marcel Lefebvre. The decree was released January 24, 2009 by the Vatican Congregation for Bishops and signed by Cardinal Giovanni Battista Re, prefect of the congregation that declared the excommunications in July 1988. The decree states that Pope Benedict, "in his paternal compassion for the spiritual discomfort expressed by the parties concerned, " hopes that this action will "consolidate reciprocal relations of trust" and "intensify and stabilize" relations between the Holy See and the Society of St. Pius X. It also says the hope is that the move will lead to the ''prompt attainment of full communion with the church by the entire Fraternity of St. Pius X.""
Keywords: Priesterbruderschaft St. Pius X; Katholische Kirche; Exkommunikation